Pengaruh Sosial Media Terhadap Keputusan Pembelian Alat Rumah Tangga Di Toko Syarifah Di Jalan Yos Sudarso II Sangatta - Resmila Abd. Rauf; Arif Rembang Supu; Muktar (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to analyze the influence of variable X (Social Media) on variable Y (purchase decisions for household appliances) at Toko Syarifah, located on Jalan Yosudarso II, Sangatta. The study was conducted with a 3-day survey, using a questionnaire consisting of 22 questions, which were distributed to 30 respondents. The results of the study showed that in one month, there were an estimated 2,790 buyers. From the results of the simple regression analysis, the regression equation was obtained as Y = 0.65 + 0.60X This equation shows that there is a positive influence between social media and purchase decisions for household appliances. This means that every one unit increase in the use of social media (X) will increase the purchase decision (Y) by 0.60. Thus, if the influence of social media is further increased, the purchase decision for household appliances will also be greater. These findings indicate that marketing strategies through social media can be an effective tool to attract consumers and influence their choices. Therefore, it is recommended that Toko Syarifah utilize social media optimally to increase brand awareness and encourage sales of household appliances. This research is expected to provide insight for business owners and other researchers regarding the importance of Social Media in modern marketing strategies.